Cell Engineering Apoptosis - Al-Rubeai, Mohamed; Fussenegger, Martin; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The series Cell Engineering is the first and only major reference work on the development of cellular systems for the production of recombinant glycoproteins, gene and cell therapies, drug screening and tissue engineering. This volume on "Apoptosis" is intended to review the state-of-the-art with in-depth assessments of this type of programmed cell death. The aim of the volume is to make the recent developments in apoptotic research readily accessible to biologists, biotechnologists and cellular engineers. The implication of apoptosis in the suppression of diseases and prolonging survival of cells in culture is presented to indicate the great potential of apoptotic research for drug production and the development of human therapies. All chapters are written as self-contained treatments of the important topics in apoptosis that are presented on an essential information basis. Topics covered range from understanding the role of signalling and effector molecules, mathematical modelling of cell death, RNAi tools in apoptosis research, to monitoring and imaging of apoptosis. This volume will be an invaluable resource for biotechnologists and researchers in apoptosis, cell biology, cell culture and molecular medicine.
Caspase Regulation at the Molecular Level -- The Bcl-2 Family -- The IGF-1 Receptor in Cell Survival: Signalling and Regulation -- Apoptosis in Hepatocytes -- Programmed Cell Death in Plants During Development and Stress Responses -- A Systems View of Cell Death -- The Role of Caspases in Apoptosis and Their Inhibition in Mammalian Cell Culture -- Improvement of Industrial Cell Culture Processes by Caspase-9 Dominant Negative and Other Apoptotic Inhibitors -- Therapeutic Small Molecule Inhibitors of Bcl-2 -- Apoptosis Control Based on Down-Regulating the Inhibitor-of-Apoptosis (IAP) Proteins: Xiap Antisense and Other Approaches -- Monitoring of Apoptosis -- Molecular Imaging of Programmed Cell Death; from Basic Mechanisms to Clinical Applications.
Keywords: LIFE SCIENCES; BIOCHEMICAL ENGINEERING; BIOCHEMISTRY; MORPHOLOGY (ANIMALS).; LIFE SCIENCES; ANIMAL ANATOMY / MORPHOLOGY / HISTOLOGY; BIOCHEMISTRY, GENERAL; BIOCHEMICAL ENGINEERING; ANIMAL BIOCHEMISTRY